A Rare Case Of Primary Squamous Cell Carcinoma Of Kidney: A Case Report (Journal of Pharmaceutical Negative Results, 2022)
Adenocarcinomas are the most prevalent kidney neoplasms. Only a few cases of primary squamous cell carcinoma have been reported.It is responsible for 6–15% of all kidney tumors. Majorly found in males as compare to females. This case report is of is of A 65-yearold man with pain on the left side of his abdomen. CT Urography showed the right kidney measuring 11.2 x 4.9 cm and striatednephrogram in initial images with evidence of multiple non enhancing areas with peripheral enhancement, largest measuring 2.2 x 1.2cm. Mild thickening of the renal pelvis is noted. Presence of diffuse tumor ranging from size 15 x 8 x 7 cm occupying almost whole ofthe kidney with unattainable origin was observed. Primary renal squamous cell carcinomas are extremely rare tumours that are rarelysuspected or identified clinically. It is an important factor to consider while making a diagnosis of kidney tumours.